2021
DOI: 10.1038/s41598-021-81578-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh sensitive refractive index nanosensors based on nanoshells, nanocages and nanoframes: effects of plasmon hybridization and restoring force

Abstract: In this study, the effect of the plasmon hybridization mechanism on the performance and refractive index (RI) sensitivity of nanoshell, nanocage and nanoframe structures is investigated using the finite-difference time-domain simulation. To create nanocage structure, we textured the cubic nanoshell surfaces and examined the impact of its key parameters (such as array of cavities, size of cavities and wall thickness) on the nanocage's RI-sensitivity. Synthesis of the designed nanocages is a challenging process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Meanwhile, this symmetric oscillation of Mode III not only couples with the external optical fields, but also shows greater RI sensitivity compared with asymmetric modes. 34,35 Thus, the wavelength shift at Mode III was more prominent than those of the cSPR, pSPR substrate and the other four conventional modes of the LRSPR substrate. Meanwhile, the E z -field distributions were inspected to help elucidate the nature of the evanescent filed.…”
Section: Resultsmentioning
confidence: 93%
“…Meanwhile, this symmetric oscillation of Mode III not only couples with the external optical fields, but also shows greater RI sensitivity compared with asymmetric modes. 34,35 Thus, the wavelength shift at Mode III was more prominent than those of the cSPR, pSPR substrate and the other four conventional modes of the LRSPR substrate. Meanwhile, the E z -field distributions were inspected to help elucidate the nature of the evanescent filed.…”
Section: Resultsmentioning
confidence: 93%
“…The resonant peaks redshifted from the near to mid-IR regions due to the reduced restoring force at ultra-small nano gaps. 40 These pronounced wavelength shifts resulted from the increase in Δ (%) or more certainly from the reduction in channel width ( W CR ), enabling an enhancement in the sensing function of the system. Here, the sensing performance was tailored by means of structural asymmetry, capitalizing on the independent resonant modes arising from non-uniform ring-disc coupling at different channel sizes.…”
Section: Resultsmentioning
confidence: 99%
“…RIS is defined as the ratio of LSPR wavelength shift to the variation of the refractive index of the surrounding medium [56]. It has been reported that the RIS of gold nanoshells is in the range of 1460-1490 nm/RIU, whereas the RIS of gold nanoparticles is 44 nm/RIU [57,58]. This shows that RIS of gold nanoshells is 33 times higher than gold nanoparticles, which indicates that gold nanoshells are more suitable for plasmonic-based applications compared to gold nanoparticles.…”
Section: Resultsmentioning
confidence: 99%